Äthiopische Inschriftenfragmente aus der himjarischen Hauptstadt Ẓafār - Müller, Walter W. (Aethiopica, 2012)
Up to now eight fragmentary Ethiopic inscriptions have been discovered in South Arabia, dating from the time immediately after the year 525 A.D. when the Yemen was conquered by the Abyssinians. Three of these fragments, among them a hitherto unpublished text, were found in the Himyarite capital Ẓafār and are parts of reports of the deeds of the Ethiopian King Kāleb. The scanty informations which can be gained from these fragmentary Ethiopic inscriptions share common features with events which are known from other contemporary epigraphic documents and from hagiographic sources in various languages.